Cardiotoxicity of Intravenously Administered CdSe/ZnS Quantum Dots in BALB/c Mice - Li, Li; Tian, Jinglin; Wang, Xiaomei; Xu, Gaixia; Jiang, Wenxiao; Yang, Zhiwen; Liu, Dongmeng; Lin, Guimiao (Frontiers in Pharmacology, 2019)
Since CdSe quantum dots (QDs) are increasingly used in electronics, medical and pharmaceutical science due to their excellent optical properties, it is necessary to carry out thorough and systematic studies on their biosafety. Numerous studies have reported the toxicity of QDs on liver, kidney, immune system and reproductive system. However, few studies have been done on the cardiotoxicity of QDs. In this study, we administered carboxylated CdSe/ZnS QDs in BALB/c mice via the tail vein and analyzed the in vivo cardiotoxicity of CdSe/ZnS QDs. The body weight, hematology, serum biochemistry, histology, heart elements concentration, echocardiography and heart oxidative stress markers were carried out at different time. There were no significant differences in body weight and heart organ index between QDs group and the control group. Hematology results showed the platelet (PLT) counts on Day 1 and Day 42 in both high dose QDs group and low dose QDs group, and the PLT counts on Day1 in the high dose group were significantly higher than that in control group. Serum biochemistry results showed that lactate dehydrogenase (LDH), creatine kinase (CK) , and creatine kinase isoenzyme (CK-MB) of mice exposed to CdSe/ZnS QDs were significantly higher than that of the control group on Day 1, and CK-MB levels still remained high on Day 7. A higher concentration of Cd was observed in the heart of CdSe/ZnS QDs exposed mice on Day 42, while no Cd was detected in the control group, which suggested that QDs can accumulate in heart. No significant histopathological changes and cardiac function were observed in all mice at different time after treatment. Increased level of glutathione peroxidase (GPx) and malondialdehyde (MDA) was observed in mice administered with high dose QDs on Day 1 and increased level of total antioxidant capacity (T-AOC) and MDA activities was observed on Day 42. These results indicated that CdSe/ZnS QDs could accumulate in heart, cause some biochemical indicators change, induce oxidative damage and have cardiotoxicity. Our findings might provide valuable information on the biological safety evaluation of the cardiovascular system of QDs.